Exchange Rate: Close to a New Onslaught? (Observatorio Económico, 2013)
Two years ago, just as 2011 was getting under way, the Central Bank of Chile launched a program of intervention in the foreign exchange market in order to prop up the nominal quotation of the U.S. currency. On January 4, 2011, the quotation stood at Ch$466.05 per dollar, jumping above Ch$490 during the rest of January; it nevertheless began a sustained decline over that first half of the year. In recent months, pressures for the Central Bank to intervene in the foreign exchange market have resurfaced. Exporting sectors feel the burden of a nominal exchange rate with a slight downward trend. Continue reading...
Keywords: Price of the dollar; Chilean economy